Estimating Groundwater Inflow to The Underground Mine Works using a 3D Groundwater Model at Vein Kubang Cicau, UBPE Pongkor - Naiborhu, Kory Yohana Adinda; Anggayana, Komang; Widodo, Lilik Eko; Wibowo, Aryo Prawoto (Geological Agency, 2024)
Estimating groundwater inflow to underground mines is essential for ensuring that mining activities can be conducted safely and continuously. Research conducted at UBPE Pongkor indicates that the veins have the fault connectivity with the Kubang Cicau vein showing potential for deeper mining, while other veins are expected to become exhausted. As the result, the Kubang Cicau vein will likely be at a lower elevation in the future. Planning decisions regarding groundwater control measures, such as dewatering, can be made in advance, contributing to a more efficient assessment of the economic feasibility of mining development. Groundwater modeling using MODFLOW software predicted a maximum groundwater discharge of 55 L/s. To address the model uncertainty, a sensitivity analysis was performed by increasing the hydraulic conductivity parameter by two order of magnitude, as this value significantly affects groundwater inflow. Conversely, decreasing the hydraulic conductivity by two order resulted in a new discharge estimate of 87 L/s. In the worst-case scenario, with the highest specific storage values, the inflow increased to 76 L/s. This demonstrates that although changes in specific storage have a notable effect on groundwater inflows, the impact is less pronounced compared to the changes in hydraulic conductivity. Nonetheless, Ss remains a key parameter, particularly in transient simulations where storage plays a more significant role in the system response to changes in water levels.